2004
DOI: 10.1016/s0006-3495(04)74097-7
|View full text |Cite
|
Sign up to set email alerts
|

N-type Inactivation Features of Kv4.2 Channel Gating

Abstract: We examined whether the N-terminus of Kv4.2 A-type channels (4.2NT) possesses an autoinhibitory N-terminal peptide domain, which, similar to the one of Shaker, mediates inactivation of the open state. We found that chimeric Kv2.1(4.2NT) channels, where the cytoplasmic Kv2.1 N-terminus had been replaced by corresponding Kv4.2 domains, inactivated relatively fast, with a mean time constant of 120 ms as compared to 3.4 s in Kv2.1 wild-type. Notably, Kv2.1(4.2NT) showed features typically observed for Shaker N-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
107
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 30 publications
10
107
2
Order By: Relevance
“…2C and 4E). According to a previous study, an N terminus truncation mutant of Kv4.2 (Kv4.2⌬40) shows slower inactivation than WT Kv4.2, and the inactivation of Kv4.2⌬40 is accelerated by an additional Kv4.2 N terminus peptide; therefore, it was concluded that the inactivation of Kv4.2 is produced by occluding the channel pore with the N terminus (24). Because binding of KChIP to the N terminus slows down the inactivation kinetics of Kv4.2, free N terminus without KChIP binding may be required for the fast inactivation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…2C and 4E). According to a previous study, an N terminus truncation mutant of Kv4.2 (Kv4.2⌬40) shows slower inactivation than WT Kv4.2, and the inactivation of Kv4.2⌬40 is accelerated by an additional Kv4.2 N terminus peptide; therefore, it was concluded that the inactivation of Kv4.2 is produced by occluding the channel pore with the N terminus (24). Because binding of KChIP to the N terminus slows down the inactivation kinetics of Kv4.2, free N terminus without KChIP binding may be required for the fast inactivation.…”
Section: Discussionmentioning
confidence: 98%
“…First, KChIP promotes the surface expression of Kv4 and increases the current amplitude of Kv4 (22,23). Second, KChIP binding slows the inactivation of Kv4 by restricting the movement of the N terminus, which may occlude the ion channel pore (24). Third, KChIP accelerates the recovery from inactivation of Kv4 (2,25,26).…”
Section: Dase-like Protein Kchip Is a Cytoplasmic Protein And Increamentioning
confidence: 99%
“…It is possible that Kv4.3/KChIP2 complex formation occurs in a different fashion depending on whether Ca 2+ is bound to KChIP2 or not. Thus, in the absence of Ca 2+ KChIP2 binding to the Kv4.3 N-terminus may not be strong enough to suppress N-type inactivation [77], while KChIP2 binding to the Kv4.3 T1-domain may still be sufficiently strong to modulate other aspects of inactivation [71,78]. Such a modulatory rather than decisive role of EF-hand-mediated Ca 2+ binding in Kv4/KChIP complex formation was also supported by the finding that binding of wild-type KChIP2c to a 90 amino acid NTF of Kv4.2 is enhanced, whereas the binding of KChIP2cΔEF mutants to that fragment, although possible, is not enhanced by Ca 2+ [35,37].…”
Section: Ca2+ Dependence Of Kv4/kchip Complex Formation and Membrane mentioning
confidence: 99%
“…Kv4 channel inactivation has been dissected in numerous biophysical studies into three separate processes: open state, closed state, and slow inactivation (15,20,21). Open state inactivation utilizes a pore block produced by the Kv4 cytoplasmic N terminus and is lost by deletion of the Kv4 N terminus or binding of KChIP proteins to the N terminus (16,22). Closed state inactivation is a separate process from open state inactivation.…”
Section: Kchip3 Rescues Function Of Znmentioning
confidence: 99%
“…The N terminus of Kv4.2 is clearly involved in inactivation gating, since deletion of this region produces slowed inactivation. Moreover, experiments on the functional properties of the N terminus show that it can act as a pore-binding peptide (15)(16)(17). Therefore, the gating changes produced by KChIPs might depend on the binding and sequestering of the Kv4 N terminus, causing an alteration to a complex set of allosteric interactions that involve other structural elements of the channel (18).…”
mentioning
confidence: 99%